Temporal muscle thickness as an independent prognostic imaging marker in newly diagnosed glioblastoma patients: A validation study. Issue 1 (30th March 2022) - Broen, Martinus P G; Beckers, Rueben; Willemsen, Anna C H; Huijs, Sandra M H; Pasmans, Raphael C O S; Eekers, Daniëlle B P; Ackermans, Linda; Beckervordersandforth, Jan; van Raak, Elisabeth P M; Verduin, Maikel; Anten, Monique H M E; Hoeben, Ann; et al.
Abstract: Background: Previous studies have recognized temporal muscle thickness (TMT) as a prognostic marker in glioblastoma, but clinical implementation is hampered due to studies' heterogeneity and lack of established cutoff values. The aim of this study was to assess the validity of recent proposed sex-specific TMT cutoff values in a real-world population of genotyped primary glioblastoma patients. Methods: We measured TMT in preoperative MR images of 328 patients. Sex-specific TMT cutoff values were used to divide patients into "at risk of sarcopenia" or "normal muscle status". Kaplan-Meier analyses and stepwise multivariate Cox-Regression analyses were used to assess the association with overall survival (OS) and progression-free survival (PFS). The association with occurrence of complications and discontinuation of glioblastoma treatment was investigated using odds ratios (OR). Results: Patients at risk of sarcopenia had a significantly higher risk of progression and death than patients with normal muscle status, which remained significant in the multivariate analyses (OS HR = 1.437; 95%CI: 1.046–1.973; P = .025 and PFS HR = 1.453; 95%CI: 1.037–2.036; P = .030). Patients at risk of sarcopenia also had a significantly higher risk of early discontinuation of treatment (OR = 2.45; 95%CI: 1.011–5.952; P = .042) and a significantly lower chance of receiving second-line treatment (OR = 0.23; 95%CI: 0.09–0.60; P = .001). There was no association with the occurrence of complications. Conclusions: Our study confirms external validity of the use of proposed sex-specific TMT cutoff values as an independent prognostic marker in newly diagnosed glioblastoma patients. This simple, noninvasive marker could improve patient counseling and aid in treatment decision processes or trial stratification.